2019
DOI: 10.3389/fimmu.2019.02873
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Robust NK-Cell Transduction With Baboon Envelope Pseudotyped Lentivector

Abstract: NK-cell resistance to transduction is a major technical hurdle for developing NK-cell immunotherapy. By using Baboon envelope pseudotyped lentiviral vectors (BaEV-LVs) encoding eGFP, we obtained a transduction rate of 23.0 ± 6.6% (mean ± SD) in freshly-isolated human NK-cells (FI-NK) and 83.4 ± 10.1% (mean ± SD) in NK-cells obtained from the NK-cell Activation and Expansion System (NKAES), with a sustained transgene expression for at least 21 days. BaEV-LVs outperformed Vesicular Stomatitis Virus type-G (VSV-G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 20 publications
(17 reference statements)
5
89
1
Order By: Relevance
“…Surprisingly, the use of BaEV pseudotyped LVs has overcome this obstacle and showed a 20-fold increase in the transduction efficiency when compared to the VSV-G pseudotyped LVs. What is more important, CAR expressing NK cells showed improvement in functionality and a higher ability to kill cancer cells [40,41]. This is proof of concept for the generation of CAR-NK cells in vitro, which may become powerful immunotherapeutic products in the future.…”
Section: Gene Therapy Using Natural Killer Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…Surprisingly, the use of BaEV pseudotyped LVs has overcome this obstacle and showed a 20-fold increase in the transduction efficiency when compared to the VSV-G pseudotyped LVs. What is more important, CAR expressing NK cells showed improvement in functionality and a higher ability to kill cancer cells [40,41]. This is proof of concept for the generation of CAR-NK cells in vitro, which may become powerful immunotherapeutic products in the future.…”
Section: Gene Therapy Using Natural Killer Cellsmentioning
confidence: 83%
“…Additionally, BaEV-LVs were able to transduce resting naïve B cells and memory B cells (20-40% efficacy) which had not been reported before [42]. In the case of T cells, recent data demonstrated that BaEV pseudotyped LVs are capable of transducing not only naïve T cells but also early thymocytes and natural killer cells with high transduction rates (up to 80%; Table 1) [39][40][41].…”
Section: Pseudotyping Of Lvs With Baboon Endogenous Virus and Feline mentioning
confidence: 91%
“…Similar high gene transfer rates to primary NK cells were reached using Vecotfusin-1 as an enhancer, which might even be increased when using a different viral envelope. For Vectofusin-1, it was recently demonstrated that transgene delivery to primary NK cells can be improved by pseudotyping LVs with the envelope protein from endogenous feline virus (RD114) or baboon endogenous retrovirus (BaEV) instead of VSV-G ( 5 , 6 ). In the field of CAR T-cells gamma-retroviral vectors or VSV-G pseudotyped LVs are most commonly used for their generation.…”
Section: Discussionmentioning
confidence: 99%
“…Transduction efficiencies of NK cells vary tremendously depending on the cell source, the viral vector system, and the transduction enhancer used ( 4 ). Lentiviral vectors (LVs) pseudotyped with the glycoprotein of the vesicular stomatitis virus (VSV-G) are classically used to generate CAR T-cells but are less efficient for NK cells with transduction efficiencies of 20–40% ( 5 , 6 ). Therefore, optimization of gene transfer protocols for VSV-G pseudotyped LV for the generation of CAR NK cells is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the virus packaging identified a higher transduction efficiency for primary NK cells when a Baboon envelope pseudotyped lentivirus (BaEV-LV) was used [105]. The previous standard was vesicular stomatitis virus GP (VSV-G) [106].…”
Section: Viral Transductionmentioning
confidence: 99%